Mild hydrothermal synthesis of NiCu nanoparticles - Huang, N.M.; Radiman, S.; Mohamed Saeed, G.H.; Gasaymeh, S.S.; Lim, H.N. (Hindawi Publishing Corporation, 2010)
Magnetic Ni-rich NiCu nanoparticles with Ni:Cu mass ratio (S) of 2.0 and 2.6 were prepared using a mixture of polyoxyethylene (10) isooctylphenyl ether (Triton X-100) and sodium dodecyl sulfate (SDS) in a mild hydrothermal condition at 95 C. X-ray diffractometry (XRD) showed that the nanoparticles prepared at S = 2.0 possessed NiCu alloy characteristic whereas the characteristic was absent at S = 2.6. The XRD data was enhanced by Fourier transform infrared spectroscopy (FTIR) which exhibited metal-metal (NiCu) band at 455 cm -1. Based on transmission electron microscopy (TEM), the average particle sizes for the nanoparticles prepared at S = 2.0 and 2.6 were in the range of 19-23nm. The as-prepared nanoparticles exhibited paramagnetic behaviour measured using a vibrating sample magnetometer (VSM) and the specific saturation magnetization decreased at the higher concentration of Ni. Â© 2010 G. H. Mohamed Saeed et al.